Control contable de ingresos y gastos de “ASOCOFECORD - Vergara Medina, Manuel Ignacio (2018)
The present research work has as its origin the analysis of the accounting control of the income and expenses of ASOCOFECORD, which is dedicated to the purchase and sale of products agricultural products, such as cocoa, the interest in the accounting record is knowledge about real values ​​based on the activities that the association carries out daily during a fiscal period. The study was carried out through observation and interviews that allowed to detect the scarce control in terms of income and expenses that are generated in the association, due to the lack of tools and personnel that help the process of accounting information, another important point Within the investigation, apart from the fact that most of them did not register, the expenses did not have the respective support document. For the sustenance of the research, emphasis can be placed on the use of sources of necessary information, knowledge, and the respective legal basis, since the purpose for which the present investigation was carried out is to know in depth what are the reasons why it is not the correct control and recording of income and expenses in the association.